Second‐trimester uterine artery Doppler, PlGF, sFlt‐1, sEndoglin, and lipid‐related markers for predicting preeclampsia in a high‐risk population. (16th September 2013) - Diguisto, Caroline; Le Gouge, Amélie; Piver, Eric; Giraudeau, Bruno; Perrotin, Franck
ABSTRACT: Objective: This study aimed to determine if screening for preeclampsia could be improved between 20 and 24 weeks of gestation by uterine artery Doppler (UAD), biomarkers and lipid‐related markers. Method: Women at high risk of preeclampsia according to obstetric and medical characteristics and history were prospectively enrolled. Transabdominal UAD, serum biomarkers (placenta growth factor (PlGF), soluble Fms‐like tyrosine kinase‐1 and sEndoglin) and lipid‐related markers (total and high‐density lipoprotein cholesterol, triglycerides and leptin) were prospectively collected between 20 and 24 weeks of gestation. The main endpoint was preeclampsia. UAD indices and biomarker levels were compared for the groups with and without preeclampsia. Multivariate analyses took into account the laboratory and ultrasound variables significantly associated with preeclampsia in the univariate analysis and age and nulliparity. Results: The study at Tours University Hospital took place from March 2003 to February 2008 and included 235 women: 56 (23.8%) developed preeclampsia, 42 were severe (17.8%) and 14 occurred before 34 weeks of gestation (5.9%). The group with preeclampsia had a higher UAD pulsatility index ( p = 0.0003), more frequent bilateral notches ( p = .0001), lower PlGF levels (239.90 vs 302.00 pg/mL; p = 0.0015), and higher triglyceride (1.95 vs 1.70 mmol/l; p = 0.0068) and leptin levels (37.40 vs 22.55 ng/mL; p = < 0.001). No significant differences were observed for other markers. Screening for preeclampsia using these Doppler and laboratory findings produced an area under the curve of 0.795. Conclusion: Second‐trimester UAD findings, and PlGF, triglyceride and leptin levels could help to predict preeclampsia. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Accuracy of screening through maternal medical and obstetric characteristics and history could be improved if these were combined with biophysical and biochemical markers. What does this study add? This prospective study showed screening for mild and severe preeclampsia in a high‐risk population could be improved by second‐trimester maternal biomarkers, lipid‐related markers and UAD.